Phenomenon of endothelial antibody capture: Principles and potential for locoregional targeting of hepatic tumors - Winkler, Nora; Gross, Wolfgang; Mier, Walter; Ryschich, Eduard (Hepatology, 2018)
The systemic drug circulation represents a source of adverse effects during tumor targeting. We studied the binding efficacy of endothelium-specific antibodies after a very short contact with an antigen target, along with assessing the intravascular capture and targeting potential of these antibodies after locoregional injection. Fast-binding anti-CD 146 (clone ME-9F1) and anti-CD31 (clone 390) antibodies were selected based on histological analysis of their binding activity. The efficacy of antibody capture by hepatic endothelium under different conditions was analyzed using an isolated liver perfusion model. The local enrichment of R-phycoerythrin and 125I-conjugated antibody was studied in vivo in two hepatic tumor models using biodistribution, scintigraphic imaging, and fluorescence microscopy. Upon injection into the tumor-feeding artery, the antibody was immediately captured in the microvasculature during the first passage. At doses not exceeding the saturation level of endothelial epitopes, the capture efficacy was almost 90%. We showed that the efficacy of endothelial capture is controlled by factors such as antibody affinity, number of binding sites on the endothelium, and microvascular flow rate. The targeting potential of endothelial capture was experimentally proven in vivo using scintigraphic imaging and biodistribution analysis after locoregional intra-arterial injection of 125I-labeled antibodies in hepatic tumor models. Conclusion: The unique phenomenon of endothelial capture can broadly prevent systemic circulation of the antibody or antibody-drug conjugates applied by intravascular injection and may have specific relevance for targeting of hepatic tumors.